-3/2w+3=1

Simple and best practice solution for -3/2w+3=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3/2w+3=1 equation:



-3/2w+3=1
We move all terms to the left:
-3/2w+3-(1)=0
Domain of the equation: 2w!=0
w!=0/2
w!=0
w∈R
We add all the numbers together, and all the variables
-3/2w+2=0
We multiply all the terms by the denominator
2*2w-3=0
Wy multiply elements
4w-3=0
We move all terms containing w to the left, all other terms to the right
4w=3
w=3/4
w=3/4

See similar equations:

| 7/6m-3=9 | | 6m-3|7=9 | | -5+3w=-11 | | x(x+1)=45 | | 6(6x-5)+4(18-5x)-3(5x+2)=-2 | | 5t+1+4t-8t=6+6 | | 4x/5+4=40 | | -3(7p+3)-2(3-20p)-3(9+6p)=0 | | 9/8x+1/2×=2 | | X×15(x+5)30=465 | | 8y-9y=20 | | 6/7x+3=1/7x+8 | | -4.5r-6.1(r-6.3)=105.21 | | (6/7)x+3=1/7x+8 | | -2x+2(7x+1)=50 | | -5x=2-3x | | 6+2x=42 | | -20-1=7t | | -20=1=7t | | 8y-9y=1 | | S=-16t^2+85t | | (x*2/3)/2=7 | | (x*0.6777777777)/2=7 | | x-3/2-7=x-8/3 | | 5x-99x-218=0 | | 0.005(x+3)=0.006+0.013 | | 4x/7-7/8=19/56 | | 3a+5=2a+20 | | 7x/9-8=48 | | 2(x+2)–3(5–x)=x+5(x–3) | | 5.8/x-62=4 | | 9(z+1)-2(z-3)=3(z-4)+3(z-3) |

Equations solver categories